Economic assessment of transporting refrigerated cargo between West-Africa and Europe: A chain cost analysis approach - Seyed Abolfazl Mohseni; Christa Sys; Thierry Vanelslander; Edwin Van Hassel (Journal of Shipping and Trade (JST), 2023)
Determining which ports to call at in a maritime loop is considered as an important determinant factor for shipping companies which impacts not only on efficiency, and productivity but also on transportation costs. The port selection process becomes more challenging and sensitive if the market is for perishable goods such as fruits and vegetables. Specifically, this paper aims to develop an efficient maritime supply chain for reefer cargo. A case study of refrigerated cargo trade between West-Africa and West-Europe is investigated for which the main objective is to minimize the trade route's supply chain costs. To do so, the paper analyzes various scenarios based upon the different types of cargo (transshipment and non-transshipment), commodity types (dry and reefer), and a combination of different (un)loading ports in and the Rotterdam-Gibraltar range. Four African ports, namely Tema (Ghana), Douala (Cameroon), Abidjan (Ivory Coast), and Dakar (Senegal), are considered for the outbound leg (Africa-Europe), while several ports in the E.U. and the U.K. are selected as inbound leg. The analysis is initiated by applying a data-gathering strategy to get the relevant container flow from European ports to West-African ports. Then, a chain cost modelling approach is used to determine what the sailing schedule of the vessel should be. By performing the import/export cargo volume and maritime and supply chain costs are calculated, which can be used by the involved stakeholders to decide which ports are the best to call on a specific route.
Keywords: 650; African ports; Chain cost model; European ports; Generalized chain cost; Maritime supply chain; Reefer and dry cargo; Total transportation cost